Treatment of severe ischemia after arteriovenous fistula by arterial ligation and bypass - Dutto, Gabriel; López Chapuis, Daniel; Esperón, Alejandro; Rojas, María (Cirugía del Uruguay, 1998)
A review is carried out on the incidence, pathogenesis and treatment of severe ischemia of upper limb fter the making of an arterio-venous fistula (AVF) as regards the treatment of two cases by means of arterial ligation distal to anastomosis and bypass. Global incidence of this complication is low, although singnificantly higher far thos AVF in proximal situation than far those performed at fists.